A novel smartphone application is reliable for repeat administration and comparable to the Tekscan Strideway for spatiotemporal gait. (31st March 2022) - Kelly, Marie; Jones, Peter; Wuebbles, Ryan; Lugade, Vipul; Cipriani, Daniel; Murray, Nicholas G.
Highlights: Data suggest that the Gait Analyzer and Tekscan Strideway are reliable over time and can comparably calculate velocity and cadence. At time point one and time point two, the devices were moderately to strongly correlated to one another for both velocity and cadence. The novel smartphone application may be used to collect reliable gait data for those in the future possibly in at-home locations. Abstract: Smartphone applications are increasingly being used to measure gait due to their portability and cost-effectiveness. Important reliability metrics are not available for most of these devices. The purpose of this article was to evaluate the test-retest reliability and concurrent validity of spatiotemporal gait using the novel Gait Analyzer smartphone application compared to the Tekscan Strideway. Healthy participants (n = 23) completed 12 trials of 10-meter walking, at two separate time points, using Gait Analyzer and while walking across the Tekscan Strideway. The results suggest excellent test-retest reliability for the Gait Analyzer and good test-retest reliability for the Tekscan Strideway for both velocity and cadence. At both time points, these devices were moderately to strongly correlated to one another for both velocity and cadence. These data suggest that the Gait Analyzer and Tekscan Strideway are reliable over time and can comparably calculate velocity and cadence.